ANALISA BIAYA DAN PENDAPATAN INDUSTRI PENGOLAHAN KAYU DI KABUPATEN KUBU RAYA - Rusnani, .; Fahrizal, M; Muin, Sudirman (JURNAL HUTAN LESTARI, 2016)
Wood furniture industry is one of the wood industries in the district of Kubu Raya, West Kalimantan Province. The industry has long existed and has to compete with other local furniture industry. The objectives of this study is to investigate the cost of each manufacture unit and actual income of each production type, analyze the economic income, indentify the amount of production break-even point and  break event point of each production unit since West Kalimantan forests have sufficient raw material of wood for furniture production. The average cost of door production is 293.111 rupiah per unit,the average cost of window production is 141.045 ruiah per unit and the average production cost of sills is 134.053 rupiah, actual profit of door production is 41.731 rupiah per unit, actual profit of window production is 49.536 per unit and actual income of sills production amounted to 105.947 per unit, break even point rupiah for door production amounted to 334.828 rupiah, break even point rupiah of window amounted to 190.581 rupiah and break even point rupiah of sills amounted to 240.000. The  findings indicate that the furniture industry is the industry that is highly helpful in increasing the incomes of enterpreneurs. Therefore, many people are interested. Community needs in the use of furniture production is increasing and the limited availability of raw materials make the selling price to be expensive. Accordingly for the furniture enterpreneurs should have sufficient supplies of raw materials in the warehouse. Keywords: Actual income, break even point and  break even point rupiah,  economic income, Production Cost.